Editorial: Why the open access movement needs South Asian scholars (The South Asianist Journal, 2013)
As this issue is being prepared for publication, a consortium of publishers - namely Cambridge University Press, Oxford University Press and Taylor & Francis - has gained an advantage in a court case over the issue of copyright infringement against Rameshwari Photocopy Services, a small shop on the Delhi University campus that sells affordable photocopied texts such as course-packs to university students. The defendant cites a provision in Section 52 of the Indian Copyright Act that provides an important exemption in the case of reproductions for educational use. However, prosecutors state that while photocopying a portion of a copyrighted text, such as a chapter, is permissible, the commercial reproduction and distribution of entire texts is ‘piracy.’ Pending a final ruling in the case, an injunction levied on the shop last year forcing it to halt photocopying services was recently upheld by the High Court in Delhi after a recent exam-time appeal by the student community and the university (Desikan 2013). Regardless of the outcome, the case comes at a time when increasingly accessible internet-based technologies offer important opportunities for education in the world's most populous region. This will pose ever-increasing challenges to established publishing practices. We'd like to suggest that these challenges are best met with a new vision; a shift toward open access publishing involving scholars of and from South Asia. This would push the issue decisively, and perhaps offer up a compelling model for scholars who remain ambivalent.